2016
DOI: 10.1038/srep25613
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Systemically Administered Nanoparticles Reveals a Size-Dependent Effect Immediately following Cardiac Ischaemia-Reperfusion Injury

Abstract: Nanoparticles represent an attractive option for systemic delivery of therapeutic compounds to the heart following myocardial infarction. However, it is well known that physicochemical properties of nanoparticles such as size, shape and surface modifications can vastly alter the distribution and uptake of injected nanoparticles. Therefore, we aimed to provide an examination of the rapid size-dependent uptake of fluorescent PEG-modified polystyrene nanoparticles administered immediately following cardiac ischae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 46 publications
4
64
0
Order By: Relevance
“…The accepted size range of NPs is not straightforward, varying across different biomedical and engineering disciplines and government agencies . Although certain sources indicate that a typical NP is 1–100 nm in three dimensions, other sources consider accepted dimensions (one or more) for NPs to include <200 nm, <500 nm, or as large as <1000 nm . The ASTM International definition provides for either two or three dimensions at the nanoscale, whereas the ISO definition indicates nanoscale in three dimensions .…”
Section: Introductionmentioning
confidence: 99%
“…The accepted size range of NPs is not straightforward, varying across different biomedical and engineering disciplines and government agencies . Although certain sources indicate that a typical NP is 1–100 nm in three dimensions, other sources consider accepted dimensions (one or more) for NPs to include <200 nm, <500 nm, or as large as <1000 nm . The ASTM International definition provides for either two or three dimensions at the nanoscale, whereas the ISO definition indicates nanoscale in three dimensions .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as the intravascular injection route requires long catheters to run through the vasculature, biomaterials that employ thermally-triggered gelling are less compatible due to concerns of material solidification in the catheter and occlusion of the lumen. For injectable biomaterials that actively or passively target the infarcted myocardium, intravenous injections have been employed in animal models [89, 90, 92]. Intravenous injection is the least invasive delivery method, although there are considerable limits in terms of the volumes and spatial control over the injectate that is ultimately delivered to the LV wall.…”
Section: Injection Methodsmentioning
confidence: 99%
“…[28][29][30] In particular, nanoparticle size partly determines the probability of sequestration by phagocytes and the clearance rate from the circulation system. 4,29 With regard to heart, recent studies suggested a size-dependent effect on nanoparticle retention in the infarcted myocardium and demonstrated that nanoparticles with a diameter within 20-200 nm are optimal for drug delivery on infarcted left ventricle. 6,21 Consistent with the results shown in these studies, the MnO nanoparticles prepared by us with the mean size of 60 nm, which falls in this range, exhibit significant higher retention in the infarcted myocardium compared with the remote area or the normal heart ( Figure 5).…”
Section: Confocal Imaging Of Myocardium Slicesmentioning
confidence: 99%
“…2,3 To solve these problems, the most direct approach is the local injection of cardioprotective agents into the infarcted area with or without supportive biomaterial. [4][5][6] However, direct myocardial injection is extremely invasive and potentially triggers further injury to the weak myocardium. 7 Therefore, emerging noninvasive treatment strategies with intravenous administration of drug delivery systems, or rather, employing nanoparticulate vehicles to encapsulate therapeutic compounds for local myocardial delivery, to fight against oxidative stress, inflammation, and apoptosis, or to improve angiogenesis represent a promising alternative choice.…”
Section: Introductionmentioning
confidence: 99%